PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI TENAGA HARIAN LEPAS PADA KANTOR DINAS PEMADAM KEBAKARAN KABUPATEN GIANYAR - Ni Komang Atika Wicahyani; Ni Putu Cempaka Dharmadewi Atmaja; I Nengah Suardhika (EMAS, 2024)
Employees as human resources are the key to the success of the organization. The company is required to manage its human resources well for the progress of the company, the success in the company's process is determined by the achievement of good performance results by employees. This study aims to test and obtain empirical evidence of the effect of compensation, organisational culture, and work motivation on the performance of casual employees at the Dinas Pemadam Kebakaran Kabupaten Gianyar. This study uses saturated or census sampling techniques, with a sample size of 60 employees. The analysis technique used in this research is multiple linear regression analysis. The results showed that compensation, organisational culture, and work motivation had a positive and significant effect on the performance of casual employees at the Dinas Pemadam Kebakaran Kabupaten Gianyar.